“Cancionero infantil para el desarrollo de la lateralidad en la inteligencia espacial” - Córdova Gallo, Joselyn Dayana (2024)
The present proposal takes into account the problems previously diagnosed in the kindergarten and high school levels where it was evidenced that the children have lateralization difficulties, which generate problems in their learning process. It is also mentioned that the teachers do not have a resource that helps to strengthen them. For this reason, the objective of the proposal is focused on making a "Children's Songbook for the development of laterality in spatial intelligence", which will help to strengthen it, through fun, creative and striking activities aimed at children from 1 to 6 years of age from different educational units of the parish of Guangaje in the 2023-2024 school year. The pedagogical approach applied is the constructivist model, which considers the child as the main protagonist in the learning process, always starting from previous knowledge, achieving the development of a quality, comprehensive and meaningful education. Where the role of the teacher is important since she must use the play-work methodology, through different didactic materials that help the understanding and individual or group participation of the students. Therefore, it was proposed to design a children's songbook for the strengthening of laterality, which consists of 12 songs classified by age, each age has two activities in which the objective, skill, importance, materials and application are made known, with the purpose of contributing to the development of motor, cognitive and social skills of the child. Consequently, the proposal was submitted for validation by users and experts from different institutions, who rated the proposal as excellent, stating that this resource should be applied to all children in kindergarten or high school, and above all that it is an innovative material in the teaching process of the teacher. It has been concluded that the implementation of a Children's Songbook within the educational process is of great help for the strengthening and development of laterality in spatial intelligence, facilitating the understanding and location within the surrounding environment in such a way that it can acquire meaningful learning from an early age, through music as an essential strategy.